MEDIATING EFFECT OF ORGANIZATION LEARNING ON THE RELATIONSHIP BETWEEN STRATEGIC CHANGE, KNOWLEDGE MANAGEMENT AND TRANSFORMATIONAL LEADERSHIP: Case of Indonesian Islamic Banks - Rianto, Muhammad Richo; Jasfar, Farida; Arafah, Willy (Journal of Economic Development, Environment and People, 2021)
Abstract Purpose - This study aims to know influence the mediation of organization learning on strategic change, knowledge management and transformational leadership and performance of Indonesian Islamic Banks Design / methodology / approach - This study uses quantitative research with a purposive sampling technique with a population of 14 Indonesian islamic banks. The targeted unit of analysis is the Islamic banks manager. There were 239 questionnaires returned and 11 of them did not meet the requirements, so only 228 were used in this study. This study uses SmartPLS 3 to test the hypothesis. Findings - This research shows that strategic change, knowledge management and transformational leadership affect organization learning. This study also shows that strategic change, transformational leadership knowledge management and organization learning have an effect on firm performance. Apart from that, the mediating role of the learning organizations also provides consistent results. Research limitation / implications - Islamic banks managers must be able to identify the importance of change for the company, because of the big risks. Supporting knowledge and leadership skills in companies makes Islamic banking better competitive. These three variables become better if the company uses a learning organization because the company will change more quickly and achieve better performance with previous experience. Originality / value - Similar research is usually carried out in manufacturing and service companies and is carried out in developed countries (Europe, America and Africa). The focus of this research is the development of strategic change supported by knowledge management and transformational leadership on performance mediated by learning organizations. This research was also conducted for the first time in Asia with the object of Islamic banks in Jakarta - Indonesia. Keyword - Strategic change, Knowledge management, Transformational leadership, Organization learning, Firm performance, Islamic Banks, Jakarta - Indonesia Paper Type - Research paper